1996
DOI: 10.1021/bi9612327
|View full text |Cite
|
Sign up to set email alerts
|

Oligomycin Sensitivity Conferring Protein of Mitochondrial ATP Synthase:  Deletions in the N-Terminal End Cause Defects in Interactions with F1, while Deletions in the C-Terminal End Cause Defects in Interactions with Fo

Abstract: The structure/function relationships of oligomycin sensitivity conferring protein (OSCP) of bovine mitochondrial ATP synthase were studied by nested deletion mutagenesis, followed by analyses of the resultant OSCPs for their ability to restore partial reactions of ATP synthesis in OSCP-depleted F1-F0 complexes. Our results indicate that, from the N-terminus of OSCP, up to 13 amino acid residues could be deleted without any effect on OSCP coupling activity. However, deletion of 16 or more residues led to a slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…A study using deletion mutants of bovine OSCP indicated that removal of the N-terminal 28 residues, corresponding approximately to all of helix 1 in E. coli ␦, impaired binding of OSCP to F 1 (29). Also a study of rat OSCP showed that the strongly conserved residue ␦-Arg-85 (Arg or Lys in 95% of sequences, residue Arg-94 in OSCP) contributed significantly to F 1 -binding energy (30).…”
Section: Discussionmentioning
confidence: 99%
“…A study using deletion mutants of bovine OSCP indicated that removal of the N-terminal 28 residues, corresponding approximately to all of helix 1 in E. coli ␦, impaired binding of OSCP to F 1 (29). Also a study of rat OSCP showed that the strongly conserved residue ␦-Arg-85 (Arg or Lys in 95% of sequences, residue Arg-94 in OSCP) contributed significantly to F 1 -binding energy (30).…”
Section: Discussionmentioning
confidence: 99%
“…Together these subunits are believed to form a "second stalk" reaching from the membrane to near the top of the F 1 sector, which may function to hold the ␣ 3 ␤ 3 subunits stationary during rotation of ␥ and ⑀ driven by proton flow through F 0 (48,49). Earlier truncation and mutagenesis studies showed that the C terminus of b was essential for proper assembly of ATP synthase (10) and implied that the C terminus of ␦ played a role in interaction of F 1 with the F 0 sector (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Membranes of mutant E. coli strains expressing truncated forms of ␦ showed little ATPase activity (21), suggesting that F 1 cannot bind to the membrane in the absence of ␦. In truncation and mutagenesis studies using the mitochondrial (22,23) and yeast (24) homologues of ␦, called OSCP 1 for oligomycin sensitivity conferring protein, the C-terminal region of OSCP was implicated in F 0 binding.…”
mentioning
confidence: 99%
“…The key sites for this interaction appear to be in the C terminus of ␦. C-terminal truncations of as few as 4 -6 residues from either ␦ or OSCP prevent the rebinding of ECF 1 or MF 1 , respectively, to F 0 (32,33).…”
Section: Discussionmentioning
confidence: 99%